DEBT-FOR-NUTRITION SWAP SEBAGAI SOLUSI PEMBIAYAAN PROGRAM PERBAIKAN GIZI DI INDONESIA - R. Muktasim Billah (Faculty of Law, Parahyangan Catholic University, 2026)
Indonesia faces a fiscal challenge in financing the Free Nutritious Meal Programme, whose projected budget of Rp 335 trillion in 2026 must be accommodated within the statutory budget deficit ceiling of 3 percent of Gross Domestic Product. Reliance on conventional debt instruments to meet this additional financing requirement risks undermining fiscal sustainability and increasing debt vulnerability. Against this background, this article proposes the Debt-for-Nutrition Swap (DfNutS) as a specialized form of debt conversion instrument that channels debt relief into nutrition-related expenditures. This study aims to examine the feasibility of adopting DfNutS in Indonesia by analyzing relevant international precedents, identifying the legal instruments required within the Indonesian regulatory framework, and formulating an operational model for its implementation. The research employs normative legal methods using statutory, conceptual, and comparative approaches. The findings indicate that Indonesia’s legal framework substantively accommodates the implementation of DfNutS through provisions governing state finance, nutrition policy, and innovative financing mechanisms based on Article 23 paragraph (1) Law Number 17 of 2003, Article 27 Presidential Regulation Number 72 of 2021, and Article 12 Regulation of Minister of Finance Number 72 of 2021. However, two critical regulatory gaps remain: the absence of a ministerial regulation on the accounting treatment and codification of non-conventional financing instruments, and the lack of a presidential instrument integrating debt-for-development swaps into the national nutrition and stunting reduction strategy. Addressing these gaps is essential to ensure the legal certainty and operational effectiveness of DfNutS in Indonesia.